Mitigation Schemes for Banggae Future Tsunami, West Sulawesi Province, Indonesia - Achmad Yasir Baeda; Nurhidayani Namiruddin (Center of Techonolgy (COT), Engineering Faculty, Hasanuddin University, 2019)
Geologically, Sulawesi Island is a complex area. It is caused by the convergence between three lithosphere plates, where the Australian Plate drifting to North, Pacific to West, and Eurasia from South to South-East respective. The future tsunami simulation was done by using SiTProS (Siam Tsunami Propagation Simulator) Version 1.5., which uses data such as earthquakes coordinate, magnitudes, focus depths, and propagation scheme, as the main input parameters in the simulations. Based on those future tsunami simulations results, the mitigation scheme chosen for Banggae District of Majene Region, West Sulawesi Province is the Vertical Tsunami Mitigation scheme. Due to its detailed parameters i.e. population details, evacuation time, distance and speed, the Vertical Tsunami Mitigation Scheme can determine the existence of shelters parameters and analyze the additional shelters needed in precise manner.